Análise estrutural de filmes finos de CdTe por meio de espectroscopia de absorção de raios-x - Coelho, Isaias Pereira (2004)
In this work, the structure of CdTe electrodeposited thin films from an aqueous solution was studied with CdSO4 and Te02 contends, for different deposition times. The used techniques for the structural characterization had been: X-rays absorption, X-rays diffraction and scan electronic microscopy (SEM). The used current density and potential in the electrodeposition had supplied a reduced thickness, same for the films with bigger time of deposition, 120 minute. The used times of growth in this work had not been enough for "hide" the global structure of the used titanium substratum. The EDX results had disclosed to the presence of Cd and Te in a not stoichiometric ratio, and also the oxygen presence was evidenced. The results of X-rays diffraction had evidenced the formation of CdTe with cubic symmetry, but with two distinct phases, first pertaining to the group F43m and second to the group Fm3m. By using the more intense peak [200], the average size of the grains of the polycrystals had been determined, supplying values of the order of 107m, for all the growth times. The measures of X-rays absorption had supplied the average distances between first neighbors tellurium atoms. One strong presence of oxigen atom was evidenced in such a way in the neighborhood of the cadmium as a the tellurium, that it diminishes with the increase of the deposition time as result of the reduction of the surface/volume ratio of the deposited film.